Identification of deleterious non-synonymous single nucleotide polymorphisms in the mRNA decay activator ZFP36L2 - Betül Akçeşme; Hilal Hekimoğlu; Venkat R. Chirasani; Şeyma İş; Habibe Nur Atmaca; Justin M. Waldern; Silvia B.V. Ramos (RNA Biology)
More than 4,000 single nucleotide polymorphisms (SNP) variants have been identified in the human ZFP36L2 gene, however only a few have been studied in the context of protein function. The tandem zinc finger domain of ZFP36L2, an RNA binding protein, is the functional domain that binds to its target mRNAs. This protein/RNA interaction triggers mRNA degradation, controlling gene expression. We identified 32 non-synonymous SNPs (nsSNPs) in the tandem zinc finger domain of ZFP36L2 that could have possible deleterious impacts in humans. Using different bioinformatic strategies, we prioritized five among these 32 nsSNPs, namely rs375096815, rs1183688047, rs1214015428, rs1215671792 and rs920398592 to be validated. When we experimentally tested the functionality of these protein variants using gel shift assays, all five (Y154H, R160W, R184C, G204D, and C206F) resulted in a dramatic reduction in RNA binding compared to the WT protein. To understand the mechanistic effect of these variants on the protein/RNA interaction, we employed DUET, DynaMut and PyMOL to investigate structural changes in the protein. Additionally, we conducted Molecular Docking and Molecular Dynamics Simulations to fine tune the active behaviour of this biomolecular system at an atomic level. Our results propose atomic explanations for the impact of each of these five genetic variants identified.